Improving teacher performance competence in Teaching students through technology information And communications in elementary school 30 Timbulun - Siti Karomah (Fakultas Sastra Universitas Ekasakti, 2017)
Basically the task of teachers to educate, teach, train and evaluate students, so that learners can become human beings who can carry out life in harmony with his nature as a human being. Related to the task of teachers in evaluating students then teachers should have the skills to teach. It is therefore necessary for the principal's role to motivate teachers to improve their performance and objectives to help teachers clearly see the purpose of education and to achieve the educational goals by fostering and developing better teaching methods and procedures. The purpose of this research is to increase the competence of teachers in the use of ICTs, so that it can improve the performance and the performance of teachers in the world compete in this globalization. So with the use of ICT teachers are able to access and create lesson material that is betterand interesting so siswapun will have a better learning achievement also especially at SD Negeri 30 Timbulun